CONSTITUTIONAL COMPLAINT AND CONSTITUTIONAL INTERPRETATION: A STUDY BASED ON PETER HÄBERLE’S OPEN SOCIETY OF INTERPRETERS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
In his work “Constitutional Hermeneutics: The Open Society of Interpreters of the Constitution: A Contribution to Pluralist and ‘Procedural’ Interpretation of the Constitution,” Peter Häberle proposes that everyone participate in constitutional interpretation. However, Article 103 of the 1988 Constitution of the Federative Republic of Brazil contains a closed list of parties authorized to initiate abstract constitutional control actions. In contrast, the constitutional complaint allows interested parties, individually or collectively, to seek the interpretation of binding decisions made in the context of abstract control. In this context, the guiding question of this work is: is the complaint an instrument for the democratization of constitutional interpretation according to Peter Häberle's hermeneutic proposal? To investigate this question, the hypothetical-deductive method was used, formulating the hypothesis that the complaint allows individuals or collectives excluded from Article 103 of the Constitution to participate in the interpretation process of binding decisions made in abstract control, serving as a tool for democratization in line with Häberle's hermeneutic proposal by allowing more voices to be heard in the interpretative process, reflecting the plurality of perspectives of those who live under the norm. The general objective is to understand the use of the complaint as a tool for democratization, while the specific objectives are to analyze Häberle's hermeneutics, constitutional interpretation, and active legitimacy in the complaint. To achieve this, sources from books and scientific articles were used. The results obtained confirm the research hypothesis, contributing to the study of constitutional law.